Palest ( Palestinians ), Their Origin and Moving's as People of Sea People in the end of the thirteenth Century B.C and the beginning of twelfth Century B.C. (Journal of Hama University, 2020)
By the end of the thirteenth Century and by the beginning of the twelfth Century B.C The region of the east coast of Mediterranean and the countries around had been made important change because of Peoples moving and migrating such of them, People who belong in origin to mid of Asia which are named by historians in usual as Indian – Europ People who came from north that see med that they reached to regions in the east of Europ from the Black Sea in order to settle in Balkan then they spread south moving on heavy carriage.Archeologists and historians of the ancient undermost east in the nineteenth century named these People as Sea People which had migrated through the Mediterranean Sea   and attacked the Kingdoms which located in east of the Mediterranean shore, and they also attacked Egypt during governing the two families the nineteenth and the twentieth, and Hithiuon in Anadol. The invasions of Sea People led to The Hithian Empire collapse and debilitating The Egyptian Empire and destructing many cities and Kingdoms of the east shore of the Mediterranean such as Ugarite.Among of the mentioned People in the Egyptian texts and letters, the name of ( Palest) ( Palestinians ) who dominated on wide lands of the south coast of Kanaan lands, and from here, This research was for studying the origin of Palestinians and showing the several theories about their original home land.